Late-Onset Multiple Self-Healing Squamous Epithelioma Ferguson-Smith Recurrence Induced by Radiotherapy - Laurence Feldmeyer; Ildiko Szeverényi; Michèle Mandallaz; E. Birgit Lane; Daniel Hohl (Karger Publishers, 2016)
We report the case of a woman in her 60s with confirmed multiple self-healing squamous epitheliomas (MSSE) Ferguson-Smith. After recurrences following surgery and radiotherapy, the patient was successfully treated with minimal surgical intervention combined with intralesional injections of triamcinolone acetate. The histological comparison between mature and regressed keratoacanthomas (KA) revealed an increased inflammatory infiltrate with numerous plasmacytoid dendritic cells in the regressed KA in comparison to the mature one, speaking in favor of an inflammation-mediated regression process. Corticosteroids injection in MSSE may have paradoxical effects with action on the proliferation phase rather than the inflammatory regression phase of the KA. Our case confirms previous reports showing that radiotherapy may exacerbate MSSE and should be avoided. Intralesional triamcinolone acetate injection is a safe and easy to use method also effective for multiple lesions. Our case underlines the difference between squamous cell carcinoma and KA, responding differently to therapies like imiquimod or radiotherapy.